Genetic variants of ACE (Insertion/Deletion) and AGT (M268T) genes in patients with diabetes and nephropathy. (June 2014) - Shaikh, Rozeena; Shahid, Syed M; Mansoor, Qaisar; Ismail, Muhammad; Azhar, Abid
Introduction: Diabetes mellitus (DM) has been a growing epidemic worldwide and poses a major socio-economic challenge. The leading cause of DM death is nephropathy due to end-stage renal disease (ESRD). This study aims to identify the possible association of I/D variants of the ACE gene and M268T (rs699) of the AGT gene of renin–angiotensin–aldosterone system (RAAS). Materials and methods: Study subjects include 115 patients with DM, 110 with diabetic nephropathy (DN) and 110 controls. Fasting blood samples were collected for biochemical analyses and PCR amplification of specific regions of the ACE and AGT genes using primers. Results: The distribution of ACE (I/D) II 28.8%, ID 35.6% and DD 35.6% while in DN II 24.5%, ID 41% and DD 34.5%. The AGT (M268T) genotypes were distributed in DM as TT 30.4%, MT 66.9% and MM 2.6% while in DN subjects TT 56.4%, MT 42.7% and MM 0.9%. Conclusion: Significant differences were observed in the DD genotype and D allele of the ACE gene and the TT genotype and T allele of AGT genes between diabetic patients with and without nephropathy. The study may conclude that the D allele polymorphism in the ACE gene and the T allele polymorphism in AGT gene may be considered as genetic risk factors for the development of nephropathy in diabetes.